Appetitive and Dietary Effects of Consuming an Energy-Dense Food (Peanuts) with or between Meals by Snackers and Nonsnackers - A. A. Devitt; A. Kuevi; S. B. Coelho; A. Lartey; P. Lokko; N. Costa; J. Bressan; R. D. Mattes (Journal of Nutrition and Metabolism)
Background. Energy-dense foods are inconsistently implicated in elevated energy intake (EI). This may stem from other food properties and/or differences in dietary incorporation, that is, as snacks or with meals. Objective. Assess intake pattern and food properties on acute appetitive ratings (AR) and EI. Design. 201 normal and overweight adults consuming a standard lunch. Test loads of 1255.2 kJ (300 kcal) were added to the lunch or provided as snack. Loads (peanuts, snack mix, and snack mix with peanuts) were energy, macronutrient, and volumetrically matched with a lunch portion as control. Participants completed meal and snack sessions of their randomly assigned load. Results. No differences were observed in daily EI or AR for meal versus snack or treatment versus control. Consumption of peanuts as a snack tended to strengthen dietary compensation compared to peanuts or other loads with a meal. Conclusions. Inclusion of an energy-dense food as a snack or meal component had comparable influence on AR and EI. Peanuts tended to elicit stronger dietary compensation when consumed as a snack versus with a meal. If substantiated, this latter observation suggests that properties other than those controlled here (energy, macronutrient content, and volume) modify AR and EI.